2009
DOI: 10.1002/art.24660
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin and salicylate differentially modulate pathogenic processes leading to vascular damage in a model of Kawasaki disease

Abstract: Objective. Kawasaki disease (KD) is a multisystem vasculitis affecting children and is characterized by immune activation in the acute stage of disease. Systemic inflammation eventually subsides, although coronary arteritis persists, resulting in aneurysm formation. KD is the leading cause of acquired heart disease among children in North America. Accepted treatment guidelines include high-dose intravenous immunoglobulin (IVIG) and aspirin in the acute phase. Although this therapy is effective, the cellular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Gupta et al (2001) found reduction of proinflammatory cytokines Il-6, Il-8 and TNF-alfa in patients with KD. Lau et al (2009) confirmed in murine model of KD that IVIG in therapeutic concentrations, but not salicylate, effectively reduced the immune response leading to TNF-alpha expression. Possible mechanism published Siedlar et al (2011) when in vitro exposure of the healthy individuals' monocytes to the IVIG preparation resulted in reduced TNF production, which was overcome by blockade of the FcγRIIB in the CD14(+) CD16(++) CD32B(high) monocytes.…”
Section: 5supporting
confidence: 50%
“…Gupta et al (2001) found reduction of proinflammatory cytokines Il-6, Il-8 and TNF-alfa in patients with KD. Lau et al (2009) confirmed in murine model of KD that IVIG in therapeutic concentrations, but not salicylate, effectively reduced the immune response leading to TNF-alpha expression. Possible mechanism published Siedlar et al (2011) when in vitro exposure of the healthy individuals' monocytes to the IVIG preparation resulted in reduced TNF production, which was overcome by blockade of the FcγRIIB in the CD14(+) CD16(++) CD32B(high) monocytes.…”
Section: 5supporting
confidence: 50%
“…6,7 The coronary arteritis is responsive to treatment with intravenous immunoglobulin, the mainstay of therapy for children with KD. 8,9 This model has also been exploited to demonstrate the beneficial effects of monoclonal antibody blockade of tumor necrosis factor-␣, an approach that is currently under study in 2 clinical trials of pediatric patients with acute KD. 10 -12 Other therapies demonstrated to be beneficial in this mouse arteritis model include matrix metalloproteinase inhibition with doxycycline and atorvastatin.…”
Section: Article See P 1542mentioning
confidence: 99%
“…[13][14][15] KD is commonly considered a systemic vasculitis, which is characterized by inflammation and necrosis of blood vessels. 16,17 It has been reported that the plasma H 2 S level of KD patients is reduced, 18 but it is still unclear whether plasma H 2 S is a potentially useful biomarker for the prediction of CAL in children with KD.…”
mentioning
confidence: 99%